Dam Operations and Subsurface Hydrogeology Control Dynamics of Hydrologic Exchange Flows in a Regulated River Reach. Issue 4 (2nd April 2019) - Shuai, Pin; Chen, Xingyuan; Song, Xuehang; Hammond, Glenn E.; Zachara, John; Royer, Patrick; Ren, Huiying; Perkins, William A.; Richmond, Marshall C.; Huang, Maoyi
Abstract: Hydrologic exchange flows (HEFs) across the river‐aquifer interface have important implications for biogeochemical processes and contaminant plume migration in the river corridor, yet little is known about the hydrogeomorphic factors that control HEFs dynamics under dynamic flow conditions. Here, we developed a 3‐D numerical model for a large regulated river corridor along the Columbia River to study how HEFs are controlled by the interplays between dam‐regulated flow conditions and hydrogeomorphic features of such river corridor system. Our results revealed highly variable intra‐annual spatiotemporal patterns in HEFs along the 75‐km river reach, as well as strong interannual variability with larger exchange volumes in wet years than dry years. In general, the river was losing during late spring to early summer when the river stage was high, and river was gaining in fall and winter when river stage was low. The magnitude and timing of river stage fluctuations controlled the timing of high exchange rates. Both river channel geomorphology and the thickness of a highly permeable river bank geologic layer controlled the locations of exchange hot spots, while the latter played a dominant role. Dam‐induced, subdaily to daily river stage fluctuations drove high‐frequency variations in HEFs across the river‐aquifer interfaces, resulting in greater overall exchange volumes as compared to the case without high‐frequency flows. Our results demonstrated that upstream dam operations enhanced the exchange between river water and groundwater with strong potential influence on the associated biogeochemical processes and on the fate and transport of groundwater contaminant plumes in such river corridors. Plain Language Summary: River stage fluctuations due to upstream dam operations enhance water exchange between rivers and aquifers. These exchange flows can stimulate biogeochemical processes in the subsurface. Here, we developed a 3‐D numerical model to simulate the flow and transport in a flood plain aquifer within the Hanford Reach, a free‐flowing section of Columbia River (WA). Our simulations revealed large spatial and temporal variability in exchange flow magnitude and direction in response to different river flow conditions. Furthermore, river channel morphology and subsurface geology together controlled the locations of high exchange flow rates. Our study provides important insights on the behavior of groundwater contaminant plumes in the river corridors of large regulated river systems. Key Points: Hydrologic exchange flows across the riverbed show strong intra‐annual spatiotemporal patterns as well as interannual variabilities Hot moments of HEFs are controlled by magnitude and timing of river stage fluctuations Hot spots of HEFs are primarily controlled by the thickness of the underlying highly permeable sediment layer